2012
DOI: 10.1128/aac.05792-11
|View full text |Cite
|
Sign up to set email alerts
|

A Semimechanistic Pharmacokinetic-Enzyme Turnover Model for Rifampin Autoinduction in Adult Tuberculosis Patients

Abstract: The currently recommended doses of rifampin are believed to be at the lower end of the dose-response curve. Rifampin induces its own metabolism, although the effect of dose on the extent of autoinduction is not known. This study aimed to investigate rifampin autoinduction using a semimechanistic pharmacokinetic-enzyme turnover model. Four different structural basic models were explored to assess whether different scaling methods affected the final covariate selection procedure. Covariates were selected by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
109
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(118 citation statements)
references
References 35 publications
7
109
1
1
Order By: Relevance
“…This suggests that doses intended to achieve the same dose in milligrams per kilogram of body weight across weight bands are not appropriate and lower-weight patients should be prescribed larger doses. This finding is driven by saturation of first-pass metabolism, which was more evident for patients in the highestweight band, the relatively increased clearance per unit of body size described by allometric scaling theory, and FFM being the most appropriate body size descriptor for scaling of clearance, which is consistent with previous evidence (11,33). Geiseler et al showed that daily dosing of a number of anti-TB drugs, including rifampin, should be based on the ideal body weight rather than the TBW (34).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This suggests that doses intended to achieve the same dose in milligrams per kilogram of body weight across weight bands are not appropriate and lower-weight patients should be prescribed larger doses. This finding is driven by saturation of first-pass metabolism, which was more evident for patients in the highestweight band, the relatively increased clearance per unit of body size described by allometric scaling theory, and FFM being the most appropriate body size descriptor for scaling of clearance, which is consistent with previous evidence (11,33). Geiseler et al showed that daily dosing of a number of anti-TB drugs, including rifampin, should be based on the ideal body weight rather than the TBW (34).…”
Section: Discussionsupporting
confidence: 81%
“…The model suggests that, on average, clearance of rifampin almost doubles from the first day of treatment to steady state, and the induction process takes around 2 weeks to reach 90% of the fully induced state. The duration of the process differs from that reported in other studies, possibly because of the richness of data and the dosing strategies used (daily versus intermittent dosing) (11,28). Though the induction half-life estimated by our model is shorter than that reported by Smythe et al, the extent of the autoinduction effect on clearance is roughly the same.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Drug exposure may be influenced by a number of variables, such as concomitant food intake, comorbidities, and intraindividual differences in pharmacokinetics (8)(9)(10)(11)(12). Therefore, it seems rational to monitor drug exposure in patients with suspected malabsorption, gastrointestinal disorders, drug-drug interactions, diabetes mellitus, or HIV coinfection (13).…”
mentioning
confidence: 99%